Interleukin-6 does not upregulate pro-inflammatory cytokine expression in an ex vivo model of giant cell arteritis. Issue 1 (6th May 2019) - O'Neill, Lorraine; McCormick, Jennifer; Gao, Wei; Veale, Douglas J; McCarthy, Geraldine M; Murphy, Conor C; Fearon, Ursula; Molloy, Eamonn S
Abstract: Objective: The aim of this study was to examine the pro-inflammatory effects of IL-6 in ex vivo temporal artery explant cultures. Methods: Patients meeting 1990 ACR classification criteria for GCA were prospectively recruited. Temporal artery biopsies were obtained and temporal artery explants cultured ex vivo with IL-6 (10–40 ng/ml) in the presence or absence of its soluble receptor (sIL-6R; 20 ng/ml) for 24 h. Explant supernatants were harvested after 24 h and assayed for IFN-γ, TNF-α, Serum amyloid A, IL-1β, IL-17, IL-8, angiotensin II and VEGF by ELISA. Myofibroblast outgrowths, cytoskeletal rearrangement and wound repair assays were performed. Results: IL-6 augmented production of VEGF, but not of any of the other pro-inflammatory mediators assayed. No differences were observed in the explants cultured in the presence or absence of the sIL-6R or between those with a positive ( n  = 11) or negative ( n  = 17) temporal artery biopsy. IL-6 did not enhance myofibroblast proliferation or migration. Western blot analysis confirmed signalling activation, with increased expression of pSTAT3 in response to IL-6+sIL-6R. Conclusion: IL-6 stimulation of temporal artery explants from patients with GCA neither increased expression of key pro-inflammatory mediators nor influenced myofibroblast proliferation or migration.